Нові відомості про поширення рідкісних видів флори Волинського Полісся - Мельник, В.І.; Баранський, О.Р.; Володимирець, В.О.; Рак, О.О.; Шиндер, О.І. (Український ботанічний журнал, 2010)
Во время флористических исследований в восточной части Волынского Полесья были обнаружены новые местонахождения 12 редких видов растений. Среди них виды, включенные в Красную книгу Украины (Astrantia major, Carlina cirsioides, Epipactis helleborine, Goodyera repens, Lycopodiella inundata), и регионально-редкие виды (Aconitum lasiostomum, Aruncus vulgaris, Clematis recta, Dianthus pseudoserotinus, Luzula sylvatica, Polypodium vulgare, Trollius europaeus). Представлены новые данные по хорологии и ценологии этих видов. New localities of 12 rare plant species were found in 2007—2008 during floristic surveys in the eastern part of Volhynian Polissya (NW Ukraine). Among them there are species listed in the Red Data Book of Ukraine (Astrantia major, Carlina cirsioides, Epipactis helleborine, Goodyera repens, Lycopodiella inundata) and regionally rare species (Aconitum lasiostomum, Aruncus vulgaris, Clematis recta, Dianthus pseudoserotinus, Luzula sylvatica, Polypodium vulgare, Trollius europaeus). New data on cho rolo gy and cenology of these species are presented.